Effect of Delta Operator on Umbral Composition in Finite Operator calculus - Maheswaran, A; Elango, C (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
The main objective of this paper is to propose the matrix representation of umbral composition and investigate the effect of delta operator on umbral composition by using the sequential representation of delta operator in finite operator calculus.